Spacial coordination between data centers and power system considering uncertainties of both source and load sides. (January 2021) - Niu, Tao; Hu, Bo; Xie, Kaigui; Pan, Congcong; Jin, Hongyang; Li, Chunyan
Highlights: A stochastic economic dispatch model in power systems with data centers is proposed. The load of data centers is regulated to promote renewable integration. Uncertainties of both renewables and DCs are considered. Benders decomposition and a new type of group based multi-cut approach is applied to solve the problem. The benefits of applying data centers in renewable integration is analyzed. Abstract: The management of the demand side in the power system, such as data centers (DCs), can improve the stability of the grid and bring economic benefits in planning and operation. Considering the increasing applications of big data and net-based technologies, the computational jobs in different region can be shifted as flexible load. In this paper, a new type of decomposition method is proposed to solve the model of the stochastic economic dispatch (ED) incorporating DCs, which considers the uncertainties of job arriving rates in DCs and wind generation in power systems. The original ED formulations are decomposed with Benders decomposition to improve computational performance, and a new type of group based multi-cut Benders decomposition is applied to improve the convergence. Case studies on a joint 18-bus system illustrate the benefits of spacial coordination between DCs and power system. The comparison between single-cut and multi-cut approach proved the effectiveness of the proposed method.